Reingeniería de procesos de la cooperativa de ahorro y crédito Jardín Azuayo Ltda. De la ciudad de Cuenca, cantón Cuenca, provincia del Azuay - Puma Guaman, Veronica Gabriela (2016)
Process Reengineering is a management tool that allows to execute a review in order to be able to develop a redesign of the processes, having as objective to reach to improve the critical points that affect the company such as: Costs, Agility and Service, etc. . For which the following investigation is proposed: "PROCESS REIGNING OF THE COOPERATIVE OF SAVING AND CREDIT JARDIN AZUAYO LTDA. OF THE CITY OF CUENCA, TOWN CUENCA, PROVINCE OF AZUAY ", having as General Objective; To propose a Process Reengineering in the Savings and Credit Cooperative Jardin Azuayo Ltda., Of the City of Cuenca, Town Cuenca, Province of Azuay, that propitiates stability in the provision of the services through the continuous improvement of the processes. In carrying out the research, the following methods and techniques were used: Logical Historical Method in order to review the Regulations governing the operation of process management in the Cooperative, Analysis and Synthesis to carry out an analysis of the current situation The Deductive in order to have knowledge of the concepts related to Process Reengineering, Inductive Method to evaluate the existing situation in the Cooperative around the particularities of Process Management. As for the collection of information necessary for the development of the research, techniques such as Interview, Survey, Direct Observation, Storm of Ideas, Pareto Diagram and Ishikawa Diagram were applied. For the data collection the Manager was interviewed, a survey was applied to 32 employees and 380 partners in order to obtain an external and internal perspective regarding the provision of services in the institution and also identified the key processes that are They perform in the Cooperative: Retreat Management, Management of Certificates of Time Deposits, Granting Consumer Credit, Managing Cards, Managing Savings, Granting Microcredits where it is identified as critical points for its operation, resulting in repetitive procedures, Are executed manually. With the information collected and after the analysis it was concluded that a Reengineering and Redesign of the Processes of Management of Certificates to term, grant credits and provision of cards; since these processes have a direct impact on the satisfaction of the partner. In the process of Certificate Management it is possible to reduce 2:04 minutes, in the process of granting credits, you get a reduction of 16 minutes and in the Provision of Cards you get a dramatic decrease of 7 days. For the implementation of Reengineering, it is necessary to acquire a computer application, which requires an investment of $ 4920.00 that optimizes the execution times of the processes, the implementation schedule is planned for 6 months in order to comply the execution of the Reengineering where the activities are defined with their respective responsible.